Agriculture and climate change beyond Copenhagen - GDPRD (2010)
Agriculture has a unique place in human development. It will be seriously affected by climate change. Adapting agriculture is critical to food security and the nutrition of the world’s population. As a major source of greenhouse gases, agriculture also carries substantial potential for mitigation. In 2009, Platform members and partners worked to enhance understanding of the relation between agriculture, climate change, food security and development. In 2010 they will continue their contribution to the climate change debate.